The Literacy Development of Primary School Level Students : an Investigation of Teaching and Learning in Rural Area. - Retno Wulandari; Intan Dewi Drupadi; Evi Ayu Anggraeni (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
Literacy is very important to be developed from an early age. Literacy is the initial abilitythat must be possessed by every individual to live life in the future. The literacy rate ofchildren in rural areas is lower than in urban areas. So literacy even in rural areas mustbe cultivated so that the literacy culture in rural communities is not left behind and isuseful in realizing the role of the younger generation in aspects of state development. Todevelop literacy, the roles of parents and teachers must work together in monitoring,facilitating, and motivating